Pengembangan Materi Ajar Cerita Anak untuk Meningkatkan Minat Baca dan Karakter Anti Bullying Pada Siswa Kelas IV SD - Maisaroh, Siti (Universitas Nusantara PGRI Kediri, 2023)
Fostering students' interest in reading with children's stories must be interesting and contain character values. Anti-bullying character is a character that must be developed because bullying often occurs in the school environment, including verbal bullying, relational bullying, and cyber bullying. In overcoming bullying actions, anti-bullying education is needed through teaching materials for children's stories that are in accordance with the character of elementary school students. This type of research is research and development (Research and Development) with the Dick and Carey model. The development subjects were Grade IV students at SDN Brudu Sumobito Jombang for the 2022/2023 academic year, which consisted of 20 students. Consists of 12 male students and 8 female students. Research and development instruments in the form of validation sheets, observation sheets, and questionnaires. Data analysis related to validity, practicality, and effectiveness tests. Based on the results of the validity test from the Material Expert it reached 87.50%, lesson plan validation reached 97.22%. The validity of observing teacher activity reaches 95% and student activity reaches 95%. The validation of the reading interest questionnaire reached 95% and the anti-bullying questionnaire reached 95%. The results of the teacher observer practicality test reached 94.23%, the student observer results reached 96.67%. The results of the test for the effectiveness of teaching materials for children's stories with anti-bullying characteristics using a N-gain score of 77.12%, so that it can be concluded that the development of teaching materials was declared effective in increasing students' interest in reading. While the N-Gain analysis of the pretest and posttest data for anti-bullying behavior obtained a result of 88.71%, meaning that the development of teaching materials was declared effective in increasing anti-bullying behavior for fourth grade students at SDN Brudu Jombang.